Rational Emotive Group Counseling Behavior Therapy on Self-Esteem and Addiction Game Online (Jurnal Bimbingan Konseling, 2019)
The purpose of this study was to determine the effectiveness of group counseling with rational emotive behavior therapy approach to increase self-esteem and reducing online gaming addiction. This study design using non-equivalent control group pre-test – post-test design. Purposive sampling technique is used to select 14 students as research subjects. Each 7 students are placed in the experimental group and a control group so that the two groups had the same initial conditions. MANOVA test results showed that group counseling rational emotive behavior therapy approach is effective in improving self-esteem (F3.10= 24.237; p < 0.01) and reducing online gaming addiction (F3.10=29.756; p < 0.01). Furthermore, the Wilcoxon test results showed that the experimental group an increase in self-esteem (z = -2.371; p < 0.05), and a decrease in online gaming addiction (z = -2.375; P <0.05) were significant. While the control group an increase in self-esteem (z =-.175; p > 0.05) and a decrease in online gaming addiction (z = -1.342; p > 0.05) did not occur significantly. The findings of this study confirms that counseling group with rational emotive behavior therapy approach is effective in improving self-esteem and lower addicted to online games.